2018
DOI: 10.3390/ijms19071900
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Calcium-Dependent Protein Kinases (CDPKs) and Their Roles in Plant Growth Regulation and Abiotic Stress Responses

Abstract: As a ubiquitous secondary messenger in plant signaling systems, calcium ions (Ca2+) play essential roles in plant growth and development. Within the cellular signaling network, the accurate decoding of diverse Ca2+ signal is a fundamental molecular event. Calcium-dependent protein kinases (CDPKs), identified commonly in plants, are a kind of vital regulatory protein deciphering calcium signals triggered by various developmental and environmental stimuli. This review chiefly introduces Ca2+ distribution in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 87 publications
(187 reference statements)
2
110
0
1
Order By: Relevance
“…In response to exogenous ABA, transcripts of an overwhelming majority of BdCDPK genes were up-regulated within 3 h, suggesting that BdCDPK genes can quickly respond to ABA signal. It seems likely that expression level of BdCDPK genes from subgroup I and II were significantly increased in response to ABA which is in agreement with the changes in AtCPK3/4/6/11/23 in subgroup I and II of Arabidopsis [63,68]. In addition, BdCDPK23/27 kept at a high expression level after ABA treatment, and their homologous AtCPK4/11 was known to positively modulate calcium-mediated ABA signaling [28].…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 70%
See 1 more Smart Citation
“…In response to exogenous ABA, transcripts of an overwhelming majority of BdCDPK genes were up-regulated within 3 h, suggesting that BdCDPK genes can quickly respond to ABA signal. It seems likely that expression level of BdCDPK genes from subgroup I and II were significantly increased in response to ABA which is in agreement with the changes in AtCPK3/4/6/11/23 in subgroup I and II of Arabidopsis [63,68]. In addition, BdCDPK23/27 kept at a high expression level after ABA treatment, and their homologous AtCPK4/11 was known to positively modulate calcium-mediated ABA signaling [28].…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 70%
“…Further, the structure of EF-hands in B. distachyon were D 1 -D 3 -S 5 -E 12 , D 1 -D 3 -S/N 5 -E 12 , D 1 -D 3 -S 5 -E 12 , and D 1 -D 3 -D 5 -E 12 , respectively (Additional file 10). And results showed that EF2 and EF4 exhibited difference with CDPKs in Arabidopsis [63]. Studies have proved that the Cterminal EF-hand structures might be important for recognizing the autoinhibitory-junction domain when the Ca 2+ regulated the activity of CDPKs [60,64,65].…”
Section: Structural Divergence and Tissue-specific Expression Of Bdcdpksmentioning
confidence: 96%
“…Number of proteins of CBL-interacting kinase, serine threonine kinase and wall-associated receptor kinase and Mitogen-activated kinase family were highly expressed wheat, involved in metal ion binding and its transportation serine/threonine kinase signalling, protein phosphorylation and response to stresses [Jin et al, 2016; Mao et al,2009; Shi et al, 2018 Hou et al, 2005; Kanneganti et al, 2008; Kumar et al, 2018; Wimalasekera et al, 2018]. Glutathione peroxidase and peroxidase family proteins expression indicates higher response to oxidative stress, glutathione peroxidase activity, metal ions binding & transportation activity [Alzahrani et al 2018; Martinez et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the subcellular Ca 2+ -dependent protein kinases (CPKs), such as CPK10, CPK30, and CPK32, are necessary for instant nitrate-stimulated cellular and metabolic responses and nitrate-induced root to shoot growth. Under sufficient nitrate conditions, Ca 2+ -sensor CPKs move to the nucleus, whereas CPK10 targets NLP7S205 phosphorylation to hold NLP7 inside the nucleus in a nitrate-dependent manner [68,69]. Furthermore, nitrate regulatory gene 2 (NRG2) also plays a critical regulatory role in plant primary nitrate responses (PPNR) based on their binding affinity for nitrate [70].…”
Section: Short Term Primary Nitrate Response (Pnr) Genesmentioning
confidence: 99%